Biofeedback algorithmization for health of elite wrestlers - Gorbachev, D. V.; Zhidkikh, T. M.; Mineev, V. S. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to develop and test benefits of a new biofeedback-assisted progress/ health controls (dysfunction prevention) training system.